Ethiopian pastoral development. Culture, environment, technology: Development interventions in pastoral Ethiopia - Coppock, D. Layne (1992)
This research article provides insights into the daily lives of one pastoral group in a remote area. Themes include: integration of women in development programs, improving access of rural people to basic essentials, and understanding the degree to which ramifications of seemingly simple technologies can be generalized, given contingencies of culture, economics, and environmental variation. Such observations are important in achieving a better understanding of Earth as human home.